Pedagogiczne (kon)teksty płci w filozofii Simone de Beauvoir - Zaworska-Nikoniuk, Dorota (Studia Edukacyjne, 2020)
In the text offered to the reader I made an attempt to re-read the central claim presented in the work of S. de Beauvoir titled The Second Sex through the prism of lessons identified for modern upbringing. The central thesis can be described as follows: the differences between genders are socially and culturally conditioned, yet determined by belonging to biological sex; maternal instinct is culturally shaped; the mother’s attitude towards the child depends on its biological sex; housework is limiting women’s potential and focus on outlook causes fear of old age. The direction of change set by de Beauvoir is the androgynous upbringing of women, changing the model of marriage, conscious motherhood, women’s professional work, and creation of feminine cultural communities.